Adherence and Quality of Life of Hypertension Patients in Gunung Jati Hospital, Cirebon, Indonesia - Dyah A. Perwitasari; Rinto Susilo; Woro Supadmi; Adrian A. Kaptein (Indonesian Journal of Clinical Pharmacy, 2015)
The treatment effectiveness of hypertension could be influenced by patients’ characteristics and patients’ adherence with medication. Besides reaching the goal of blood pressure decrease after the treatment, their quality of life has become the main concern regarding effectiveness of hypertension treatment. This study aimed to explore the hypertension patients’ adherence and quality of life. In addition, it was studied which factors associated with adherence and quality of life in hypertension patients treated withantihypertensive at Gunung Jati Hospital, Cirebon. We recruited 85 adult hypertension patients who were treated with antihypertensive agents for at least 6 months. The patients’ adherence was measured by Medication Adherence Report Scale and the patients’ quality of life was measured by Indonesian version of Short Form-36 questionnaire. The patients’ adherence was found as 24.03 (SD: 1.98) and there were no significant differences of patients’ adherence using monotherapy and combination therapy. Thepatients’ characteristics such as, age, gender and education level could not predict patients’ adherence (p>0.05). The average of Physical Component Summary (PCS) and Mental Component Summary (MCS) were 43.35 (SD: 9.4) and 52.13 (SD:5.59). Age and gender may predict PCS, however, education and comorbidity may predict MCS (p<0.05). Hypertension patients’ adherence in Gunung Jati hospital is good. The PCS and MCS scores in this study are comparable to the other previous studies. The patients’characteristic could not be the predictor of patients’ adherence.Keywords: Adherence, hypertension, quality of life, MARS, SF-36Kepatuhan dan Kualitas Hidup Pasien Hipertensi Di Rumah Sakit Gunung Jati CirebonEfektivitas terapi pasien hipertensi dapat dipengaruhi oleh beberapa faktor karakteristik pasien dan kepatuhan pasien. Selain menurunkan tekanan darah, luaran lain dari terapi hipertensi adalah meningkatkan kualitas hidup pasien. Tujuan penelitian ini adalah untuk mengetahui kepatuhan dan kualitas hidup pasien hipertensi serta memahami faktor prediksi kepatuhan dan kualitas hidup pasien. Sejumlah 85 pasien hipertensi yang telah mengonsumsi obat hipertensi minimal 6 bulan berpartisipasi dalam penelitian ini. Kepatuhan pasien diukur dengan kuesioner Medication Adherence Report Scale versi Indonesia dan kualitas hidup pasien diukur dengan kuesioner Short Formulary-36 versi Indonesia. Kepatuhan pasien hipertensi di RS Gunung Jati Cirebon adalah 24,03 (SD:1,98) dan tidak terdapat perbedaan signifikan antara kepatuhan pasien hipertensi yang menggunakan monoterapi dan kombinasi terapi. Karakteristik pasien seperti usia, jenis kelamin, dan tingkat pendidikan bukan merupakan prediktor kepatuhan (p>0,05). Rata-rata Physical Component Summary (PCS) dan Mental Component Summary (MCS) adalah 43,35 (SD: 9,4) dan 52,13 (SD:5,59). Usia dan jenis kelamin merupakan prediktor PCS dan pendidikan serta komorbiditas merupakan prediktor MCS (p<0,05). Kepatuhan pasien hipertensi di RS Gunung Jati Cirebon cukup baik. Komponen PCS dan MCS cukup baik dibandingkan dengan penelitian lain. Karakteristik demografi pasien bukan merupakan prediktor kepatuhan pasien.Kata kunci: Hipertensi, kepatuhan, kualitas hidup, SF-36, MARS